Effect of Near Work on Intraocular Pressure in Emmetropes. (28th January 2020) - Priluck, Aaron Z.; Hoie, Aidan B.; High, Robin R.; Gulati, Vikas; Ghate, Deepta A.
Abstract : Objective . To determine whether accommodation induced by reading alters intraocular pressure (IOP) in healthy, young, emmetropic adults and to document the duration and magnitude of this effect. Design . Cross-sectional study. Participants . Fifteen healthy, emmetropic young adults. Methods . Subjects performed 20 minutes of near work (reading at 33 cm) followed by 20 minutes of far work (reading at 520 cm) while IOP was measured using an iCare tonometer at baseline and every 5 minutes thereafter. Statistical analysis was performed using repeated measures ANOVA. Main Outcome Measures . Intraocular pressure. Results . IOP decreased significantly compared to baseline IOP after 10 minutes of near work (average change of −1.60 ± 2.2 (SD) mm Hg, p < 0.05 ). IOP remained lower than baseline IOP throughout all subsequent near and far work. The difference in IOP at the end of experimentation compared to baseline IOP was −1.87 ± 1.81 mm Hg (p < 0.05 ). The minimum IOP reached during experimentation compared to baseline was on average −3.8 ± 2.2 (SD) mm Hg (range: 0 to −8.0 mm Hg). 13 of 15 subjects (87%) and 9 of 15 subjects (60%) had at least one IOP measurement of at least 2 mm Hg and 4 mm Hg less than their baseline IOPs, respectively. Conclusions . Near work decreases IOP in healthy emmetropes, and this effect is sustained for at least 20 minutes after discontinuing prolonged near work. Providers may need to consider this effect when measuring IOP in clinical practice.